Ward Robert E. y Shulman, Frank Joseph, The allied occupation of Japan, 1945-1952. An Annotated Bibliography of Western-Language Materials. American Library Association, Chicago, 1974. - Martínez Legorreta, Omar (Estudios de Asia y África, 1974)
-